High‐resolution MALDI‐FT‐ICR MS imaging for the analysis of metabolites from formalin‐fixed, paraffin‐embedded clinical tissue samples. Issue 1 (30th June 2015) - Buck, Achim; Ly, Alice; Balluff, Benjamin; Sun, Na; Gorzolka, Karin; Feuchtinger, Annette; Janssen, Klaus‐Peter; Kuppen, Peter JK; van de Velde, Cornelis JH; Weirich, Gregor; Erlmeier, Franziska; Langer, Rupert; et al.
Abstract We present the first analytical approach to demonstrate the in situ imaging of metabolites from formalin‐fixed, paraffin‐embedded (FFPE) human tissue samples. Using high‐resolution matrix‐assisted laser desorption/ionization Fourier‐transform ion cyclotron resonance mass spectrometry imaging (MALDI‐FT‐ICR MSI), we conducted a proof‐of‐principle experiment comparing metabolite measurements from FFPE and fresh frozen tissue sections, and found an overlap of 72% amongst 1700 m/z species. In particular, we observed conservation of biomedically relevant information at the metabolite level in FFPE tissues. In biomedical applications, we analysed tissues from 350 different cancer patients and were able to discriminate between normal and tumour tissues, and different tumours from the same organ, and found an independent prognostic factor for patient survival. This study demonstrates the ability to measure metabolites in FFPE tissues using MALDI‐FT‐ICR MSI, which can then be assigned to histology and clinical parameters. Our approach is a major technical, histochemical, and clinicopathological advance that highlights the potential for investigating diseases in archived FFPE tissues. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.